Control panel at Hercules Parlin plant - Hercules Incorporated (1961)
General view of an unidentified employee operating a control panel at the Hercules Powder Company plant in Parlin, New Jersey. Per notations accompanying the photograph, this control panel was used for various plant operations to produce Penton, a chlorinated polyether used as an ingredient in protective coatings for structural steel and other metals, papers, cardboard, and plastics. Formed in 1912 as part of an anti-trust settlement with DuPont, the Hercules Powder Company (later Hercules Inc.) initially specialized in the manufacture of explosives and smokeless powders and subsequently diversified its business to encompass a variety of industrial products, including pine and paper chemicals, synthetics, pigments, polymers, and cellulose.
Keywords: Employees; Chemical industry; Scientific apparatus and instruments; Control boards (Electrical engineering); Corporations; Hercules Incorporated